2012
DOI: 10.1111/j.1440-1681.2012.05748.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum nitric oxide synthase activity is a novel predictor of impaired vasorelaxation in rats

Abstract: Summary It is well documented that both acetylcholine (ACh)‐evoked arterial relaxation and brachial artery flow‐mediated vasodilatation are blunted in hypercholesterolaemic patients. However, there are no simple diagnostic methods to detect the pathology of blood vessels of patients. To establish the use of serum nitric oxide synthase (NOS) activity as a diagnostic parameter for impaired vasorelaxation, animals with different levels of vascular healthiness were made by feeding Sprague–Dawley rats a normal die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…1 First, although the authors delicately investigated the links between lower serum nitric oxide synthase (NOS) activity, high cholesterol and decreased relaxation of isolated aortic rings, the results reported by the authors are not surprising. It has been reported previously that, in cultured neuroblastoma cells, mevastatin and serum rapidly increase neuronal NOS expression.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…1 First, although the authors delicately investigated the links between lower serum nitric oxide synthase (NOS) activity, high cholesterol and decreased relaxation of isolated aortic rings, the results reported by the authors are not surprising. It has been reported previously that, in cultured neuroblastoma cells, mevastatin and serum rapidly increase neuronal NOS expression.…”
mentioning
confidence: 89%
“…
We would like to make the following comments regarding the recent communication Serum nitric oxide synthase activity is a novel predictor of impaired vasorelaxation in rats, published in a recent issue of the Journal. 1 First, although the authors delicately investigated the links between lower serum nitric oxide synthase (NOS) activity, high cholesterol and decreased relaxation of isolated aortic rings, the results reported by the authors are not surprising. It has been reported previously that, in cultured neuroblastoma cells, mevastatin and serum rapidly increase neuronal NOS expression.
…”
mentioning
confidence: 99%
“…Elevated plasma cholesterol and glucose-induced oxidative stress are common causes of endothelial dysfunction with decreasing NO production in the endothelium (Chan et al, 2012;Seto et al, 2009). A study found that piceatannol-3'-O-beta-D-glucopyranoside (PG) could inhibit arginase (a regulator of the eNOS) activity, increase NO production, and decrease reactive oxygen species generation in thoracic aorta of apolipoprotein E-null mice (ApoEÀ/À) fed with high-cholesterol diet (HCD).…”
Section: Prevention Of Endothelial Dysfunctionmentioning
confidence: 99%
“…Through decreasing serum malondialdehyde content and enhancing superoxide dismutase activity in vivo , Raphani Semen alkaloids are believed to have good cardiovascular protective effects from oxidative damage. In addition, choline, a metabolite from the degradation of sinapine in Raphani Semen extract in the digestive system, might activate the NO-NOS system [90], thereby increasing the synthesis of NO and resulting in vasodilation [9]. However, whether the anti-hypertensive effect of water-soluble alkaloids from Raphani Semen resulted from the increase in NO availability by directly enhancing NO production (stimulation of NOS activity), by indirectly reducing NO degradation (antioxidant properties), or by both pathways was currently unknown and warranted further investigations.…”
Section: Pharmacological Activities Of Raphani Semenmentioning
confidence: 99%